Role of omega 3 fatty acid in chemo-therapy induced cognitive decline - Ayesha Shahid; Hira Jameel; Hadiqa Nousheen (Journal of the Pakistan Medical Association, 2020)
Dear Madam, One of the toxic side effect of chemotherapeutic agents in the brain, now more frequently encountered due to a rising number of cancer survivors who recieved chemo, is chemo induced cognitive decline, known more popularly in clinics as chemobrain or chemofog (1). Cancer-related cognitive impairment (CRCI) is encountered in survivors of chemotherapy treated central nervous system and non central nervous system malignancies (1). CRCI can happen any time during and after the chemo (2). CRCI affects the executive function, memory, attention, concentration, language, processing speed and other domains of cognition culminating in reduced treatment compliance, poorer quality of life and ultimately decreased life span (2). Continuous...